Corrigendum to “Functionalized carbophenes as high-capacity versatile gas adsorbents: An ab initio study” [Comput. Mater. Sci. 232 (2023) 112665] (S0927025623006596), (10.1016/j.commatsci.2023.112665) - Junkermeier, Chad E.; Larmand, Evan; Morais, Jean-Charles; Kobebel, Jedediah; Lavarez, Kat; Adra, R. Martin; Yang, Jirui; Diaz, Valeria Aparicio; Paupitz, Ricardo [UNESP]; Psofogiannakis, George (Elsevier, 2024)
The authors have identified errors in Figures 6 and 9 of that publication. The wrong CO2 total energy was used when calculating adsorption energies in Equation 2 of that publication, resulting in the DFTB+-based CO2 adsorption energies being too large by 0.1347 eV. The corrected graphs are given as Figures 1 and 2 of this corrigendum.[Formula presented] .[Formula presented] The authors would like to apologise for any inconvenience caused.